(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The upgrading the competency of the instructors in response to the policy of developing the university supervisor teachers and students which was consistent with quality assurance. In this regard, the university supervisor of the TNSU can be used process of instruction to be guideline for improving and developing the physical education teaching and learning curriculum. Moreover, it was able to present the results for academic benefits in the field of curriculum management for the undergraduate students. The main objective aimed to study the development of the competency of the university supervisors. The study used (i) The Delphi technique as principally for determination the indicators to develop the competency indicators, (ii) An in-depth interview was used to study the competency of the university supervisors and (iii) Confirmatory Factor Analysis (CFA) was used for verify the consensus of the model competency. The investigators found that the competency of the university supervisors of the faculty of education, Thailand National Sport University were consisted of knowledge, experience, planning, management, monitoring and evaluation, moral, ethics and conduct.